The battle for privacy. Issue 6 (June 2016) - Mansfield-Devine, Steve
Abstract : Privacy in the digital realm has been an issue bubbling away for decades, pretty much since we've been communicating with computers. Sometimes it has erupted into controversy, such as the public feud over encryption and the Clipper chip in the 1990s. 1 Now, however, it would seem that significant battle lines are being drawn – not between the public and the authorities, as one might expect, but between government agencies and technology companies. In this interview, Javvad Malik, security advocate at AlienVault, discusses the recent Apple/FBI controversy and the ethical issues it raises for the tech industry. Now, it seems, significant battle lines are being drawn – not between the public and the authorities, as one might expect, but between government intelligence and law enforcement agencies and technology companies. In this interview, Javvad Malik of AlienVault discusses the recent Apple/FBI controversy and the ethical issues it raises for the tech industry. And he explains how we as technology users have an important role to play in keeping ourselves safe online.